Cry Babies and Pollyannas: Infants Can Detect Unjustified Emotional Reactions. (27th May 2013) - Chiarella, Sabrina S.; Poulin‐Dubois, Diane
Abstract : Infants are attuned to emotional facial and vocal expressions, reacting most prominently when they are exposed to negative expressions. However, it remains unknown if infants can detect whether a person's emotions are justifiable given a particular context. The focus of the current paper was to examine whether infants react the same way to unjustified (e.g., distress following a positive experience) and justified (e.g., distress following a negative experience) emotional reactions. Infants aged 15 and 18 months were shown an actor experiencing negative and positive experiences, with one group exposed to an actor whose emotional reactions were consistently unjustified (i.e., did not match the event), while the other saw an actor whose emotional reactions were justified (i.e., always matched the event). Infants' looking times and empathic reactions were examined. Only 18‐month‐olds detected the mismatching facial expressions: Those in the unjustified group showed more hypothesis testing (i.e., checking) across events than the justified group. Older infants in the justified group also showed more concerned reactions to negative expressions than those in the unjustified group. The present findings indicate that infants implicitly understand how the emotional valence of experiences is linked to subsequent emotional expressions.